STATE RESPONSIBILITIES FOR THE MANAGEMENT OF OIL AND GAS IN THE BORDER REGION - Zulkarnain, Zulkarnain (Tadulako University, 2020)
Indonesia's natural resources which are very strategic and have an important role on the national economy include natural resources in the form of oil and natural gas which must be used as much as possible for the prosperity of the people of Indonesia. This is confirmed in Article 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia which states that the earth, water and natural resources contained therein are controlled by the state and used for the greatest prosperity of the people. Potential oil reserves in border areas should be given a special share of the results of oil and gas management so that development in the border region is quickly encouraged to match the development of urban areas. Current regulations in the field of oil and gas management (Law Number 22 Year 2001 concerning Oil and Gas) are very liberal and are very far from the mandate of the 1945 Constitution which requires the prosperity of the people. In the implementation of state control over oil and gas management in border areas, the policy aspects can be as follows: Regulation (Regeleensdaad), Management (Bestuurdaad), Management (Behersdaad), and Supervision (Toezicthoudensdaad), Decision / stipulation (Beschikking). This research is a normative legal research that specifically examines the laws and regulations governing natural resource management in Indonesia, with the aim of finding out how the state is responsible for oil and gas management in border areas. The results showed that the results of the management of oil and gas mining managed by business actors in general, and foreign investment companies in particular benefit the company more than the people's welfare. Foreign domination in the exploitation of national energy, especially oil, is due to unfavorable work contracts, weak energy security vision designed by the government, institutional integration in upstream and downstream management, regulations are still ad-hoc and planning is weak, weak control system and good governance (good governance) in the energy sector.